2003
DOI: 10.1161/01.cir.0000095786.44712.2a
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Improved Renal Function After Percutaneous Stent-Supported Angioplasty of Severe Atherosclerotic Ostial Renal Artery Stenosis

Abstract: Background-Percutaneous stent-supported angioplasty is a treatment option for atherosclerotic ostial renal artery stenosis. Improvement of renal function by such intervention, however, is controversial and thought to be limited to specific subsets, such as nondiabetic patients and bilateral stenoses. In this prospective study, we investigated predictors for improvement of renal function and blood pressure after renal artery stent placement. Methods and Results-The study included 215 consecutive patients with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(68 citation statements)
references
References 34 publications
6
61
1
Order By: Relevance
“…Furthermore, following PTRA, creatinine clearance improved significantly compared with baseline in the 18 of the 25 patients that were eligible at the 6-month follow-up (median: 52 ml/min, range: 26–164, vs. median: 63 ml/min, range: 18–151, for baseline and 6 months after revascularization, p < 0.05). Other studies have similarly demonstrated that serum creatinine values can be used to predict improvement in renal function following PTRA [124, 125]. Furthermore, ARAS patients undergoing PTRA with creatinine values >300 µmol/l (3.9 mg/dl) have almost 5-fold higher mortality rates compared with patients with creatinine values <300 µmol/l (relative risk = 4.7, 95% CI = 2.0–11.0, p < 0.0005) [126].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Furthermore, following PTRA, creatinine clearance improved significantly compared with baseline in the 18 of the 25 patients that were eligible at the 6-month follow-up (median: 52 ml/min, range: 26–164, vs. median: 63 ml/min, range: 18–151, for baseline and 6 months after revascularization, p < 0.05). Other studies have similarly demonstrated that serum creatinine values can be used to predict improvement in renal function following PTRA [124, 125]. Furthermore, ARAS patients undergoing PTRA with creatinine values >300 µmol/l (3.9 mg/dl) have almost 5-fold higher mortality rates compared with patients with creatinine values <300 µmol/l (relative risk = 4.7, 95% CI = 2.0–11.0, p < 0.0005) [126].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…(10,11,13,18), while no significant reduction in LVM occurred in 84 patients participating in the study of Marcantoni et al in 2012 (12). The reduction in systolic blood pressure was reported as an important associated factor in LVM improve- The function of aldosterone in causing left ventricular hypertrophy, independent of high blood pressure can be helpful in interpreting these findings (10).…”
Section: Discussionmentioning
confidence: 96%
“…Although previous studies on the predictors of improved out-of-office BP after PTA are limited, high baseline BP and normal renal parenchymal thickness in ARAS 14 and short duration of hypertension in FMD 37 have been reported to be predictors of better BP reduction diagnosed using ambulatory BP monitoring and office BP, respectively. Our results suggested that, for the success of PTA treatment, out-of-office BP measurement after PTA is particularly important for patients with ARAS, longer duration of hypertension, or proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The evidence on the effects of PTA on not only out-of-office BP 14,15 but also BP variability is limited.…”
mentioning
confidence: 99%